PENGARUH KURIKULUM MERDEKA BELAJAR TERHADAP PENINGKATAN AKADEMIK SISWA KELAS X DI SMKN 5 DUMAI - Ananda, Gheri Febri; Khaira, Rizka; Yannuar, Yannuar (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2024)
This research aims to determine the impact of the Merdeka Belajar curriculum on improving the academic achievement of level X students. This research uses a quantitative approach with descriptive and inferential statistical analysis. A sample of 55 students was randomly selected from the entire class X population at SMKN 5 Dumai, consisting of 5 students from each department. The collected data was then analyzed using a one-sample t-test by comparing the average score of the population in the semester before implementing the Merdeka Belajar curriculum with the scores in several samples after the Merdeka Belajar curriculum was implemented. The analysis results show a statistical t-test value of 14.05, which exceeds the critical t value (critical value) with a significance level of α = 0.05 (1.675), or in other words, the p-value is smaller than α. Therefore, the conclusion that can be drawn is that there is sufficient strong evidence to reject the null hypothesis (H0) and conclude that the average student score in the 2022/2023 academic year after implementing the Merdeka Belajar curriculum is higher than the average in 2021/ 2022 before the implementation of the Merdeka Belajar curriculum, at a significance level of 0.05.